AN ANALYTICAL STUDY OF IMPACT OF RECESSION ON TOURISM & HOSPITALITY INDUSTRY - Dr. , Priyanka Daya Choudhary (International Journal of Psychosocial Rehabilitation, 2013)
The hotel industry is directly connected by the tourism industry. It is due to the reason that with a decrease in the number of tourists, the arrival of customers at the hotels gets reduced, which directly affects the profitability of the hotels. The current business scenario accompanied by the economic recession has drastically affected the operations and business status of different industries. The hotel industry has also got affected by the economic recession. The efficiency and profitability of many companies got reduced significantly, which intended the companies towards cutting the cost and reducing the labor force. In spite of the drastic conditions imposed by the economic recession, the hotel industry managed to survive in the market. Hotel industry is one of the most important segments of hospitality industry, which offers accommodation, amusement and recreation facilities to the potential customers. The main aim of the hotel industry operators is to provide quality services, maintaining the adjustable facilities and directing the lodging related operations for the customers. In the present competitive environment, the hotel industry is widely dominated by the large group of hotel chains. The paper intends to focus on growth of hotels in India during recession period. The paper will also highlight the strategies and practices in order to overcome the influence of economic recession.